Strengthen The Capacity of Traditional Fishermen Who are Facing the Threat of Coastal Ecosystem Damage in Bangka Island Based on Local Capacity - Endang Bidayani; Devi Valeriani; Reniati (Universitas Djuanda Bogor, 2025)
The impact of tin mining activities in coastal regions on Bangka Island is cause for concern due to the damage inflicted on the coastal ecosystem. The study aims to analyze: 1) the resilience strategies used by traditional fishermen impacted by tin mining along the coast of Bangka Island; 2) Examining the attributes of conventional fishermen with adaptable abilities; 3) Studying the factors that contribute to the resilience of traditional fishermen; 4) Also, provide suggestions to enhance the skills of traditional coastal fishermen regarding tin mining, focusing on local capacity. The current approach for research includes carrying out surveys. The site selection is centered on coastal regions that have been shaped by tin mining, with a particular emphasis on the central area of Bangka. The data analysis technique involves exploring and describing information. Findings of the study indicate that: 1) Traditional fishermen utilize an active resilience strategy; 2) Key qualities of resilient traditional fishermen include Insight, Independence, Relationships, Initiative, Creativity, Humor, and Morality; 3) Family plays a crucial role in supporting the resilience of traditional fishermen; and 4) A recommended policy to enhance the resilience of traditional fishermen involves implementing a social empowerment program with a degrowth perspective, focusing on initiatives like fostering agricultural enterprises, marine cultivation, and coastal tourism. A recommended policy to enhance the resilience of traditional fishermen involves implementing a social empowerment program with a degrowth perspective, focusing on initiatives like fostering agricultural enterprises, marine cultivation, and coastal tourism.